Successful Implementation of Extracorporeal Membrane Oxygenation Support as a Bridge to Heart-Lung Transplantation in an Eisenmenger's Syndrome Patient With Paradoxical Coronary Embolism. (May 2019) - Zhang, James; Patel, Sumit; Clavijo, Leonardo; Laughrun, David
We report a case of a 23-year-old female with a history of unrepaired ventricular septal defect and pulmonary arterial hypertension with Eisenmenger's syndrome (ES) presenting with chest pain. Electrocardiography demonstrated new anterior Q waves and anterolateral ST elevations, and coronary angiography revealed a large organized thrombus in the mid-left anterior descending artery consistent with paradoxical coronary embolism. Patient was treated with percutaneous coronary intervention and aggressive anticoagulation management. Intensive care unit course was complicated by respiratory failure requiring intubation due to hospital-acquired pneumonia in the setting of severe pulmonary hypertension. Patient was emergently initiated on veno-venous extracorporeal membrane oxygenation support (ECMO) as a bridge to heart-lung transplantation. After initiation of ECMO, patient displayed significant clinical improvement and underwent successful heart-lung transplantation. This case highlights veno-venous ECMO as a bridge to heart-lung transplantation in acutely decompensated patients with ES, and is the first reported case of paradoxical coronary embolism in a patient with ES.